Wspomaganie procesów integrowania systemu gospodarki odpadami przez zarządzanie informacjąw systemie - Kobyłko, Grzegorz; Sej-Kolasa, Małgorzata (Supporting the integration processes in waste management system through system information management.", 2008)
The article attempts to asses the importance of information quality and flow for reasonable waste management. The authors express an opinion that low-quality information may hinder waste management, while poor data flow significantly affects the information quality. They focus on the opportunities for improving the information quality through the integration of internal information systems owned by individual entities involved in the waste management system.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 72-80